The Relationship Between Speech Delay with Cerebral Palsies in Children at Rs Haji Medan - Armand Surya Nugraha; Nurcahaya Sinaga (Journal of Social Research, 2023)
Speech delay in children is a condition in which the child's expressive language development is inappropriate or below his age. The incidence of speech delay for Indonesian children who are not in school yet reaches 5–10%. There are more male children with speech disorders than females. The causes of speech delay can be hearing loss, cerebral palsy, low thinking ability, or autism. Cerebral palsy patients may experience uncontrollable movements and muscle spasms in the mouth. This will have an impact on the development of children's speech. This research is a descriptive-analytical study with a cross-sectional approach. The subjects of this study are patients with cerebral palsy in RS Haji Medan, with a total sample size of 132 people. Data analysis using the Chi-square tes. There was a significant relationship between speech delay and cerebral palsy among pediatric patients in RS Haji Medan. The result using Fisher’s exact test showed a P value less than 0.05, which validated the hypothesis. There was a significant relationship between speech delay and cerebral palsy among pediatric patients in RS Haji Medan.